2014
DOI: 10.2147/jpr.s73044
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of quantitative sensory models to morphine analgesia in humans

Abstract: IntroductionOpioid analgesia can be explored with quantitative sensory testing, but most investigations have used models of phasic pain, and such brief stimuli may be limited in the ability to faithfully simulate natural and clinical painful experiences. Therefore, identification of appropriate experimental pain models is critical for our understanding of opioid effects with the potential to improve treatment.ObjectivesThe aim was to explore and compare various pain models to morphine analgesia in healthy volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…This requires robust and reliable experimental models to mimic clinical pain as well as valid methods to assess the pain response. It has been demonstrated that tonic pain models reflect clinical pain to a higher degree, and they are more sensitive to analgesic treatments 16. The cold pressor test (immersion of hand in ice water) can be used to evoke tonic pain with reproducible pain ratings 7,8.…”
Section: Introductionmentioning
confidence: 99%
“…This requires robust and reliable experimental models to mimic clinical pain as well as valid methods to assess the pain response. It has been demonstrated that tonic pain models reflect clinical pain to a higher degree, and they are more sensitive to analgesic treatments 16. The cold pressor test (immersion of hand in ice water) can be used to evoke tonic pain with reproducible pain ratings 7,8.…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen of the healthy subjects in the present study have been part of previous studies where electrical stimulation was performed before the thermal stimuli. 27,29,40 This may be a potential source of error, but we consider the effect very small as electrical stimulation activates the nerve endings directly, in contrast to thermal and mechanical stimuli, which activates peripheral receptors in the GI wall. Mechanical stimulation is probably more robust because it is preceded by preconditioning that minimizes the effects of elastic tissue properties, and ensures more reliable assessment of the sensory response.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study the comprehensive protocol and the custom designed probe did not allow measurement of the cross‐sectional area and therefore the volume was used as proxy for the strain assessments. This approach has successfully been used in a series of basic and pharmacological experiments …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the discrepancy in response between these two studies may be attributed to the mode of drug administration. Additionally, it is plausible that transcutaneous electrical stimulation (phasic, and excites all peripheral fibers in a non‐differential fashion) is less sensitive to morphine effects as it has been demonstrated that pain models with deep tonic stimulation including C‐fiber activation and and/or endogenous pain modulation were more sensitive to morphine analgesia . Therefore, results may also be explained by the phasic nature of the electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%